Integrated land use assessment (ILA) for planning and monitoring urban development - Ahris Yaakup,; Siti Zalina Abu Bakar,; Susilawati Sulaiman, (Environmental Management Society, Malaysia, 2005)
The dynamic nature of planning and monitoring of development in Klang Valley region requires for a „tool‟ for continuous evaluation and analysis of the current environment as well as the capacity for future development. As such, Integrated Land use Assessment (ILA) is introduced as a new concept within the “Application of Geographic Information System (GIS) for Klang Valley Region” (AGISwlk). The introduction of ILA as an integrated land use planning approach that exploits the GIS analysis capabilities, supported by the use of planning support systems is seen as a good mechanism for monitoring urban development especially in environmentally-sensitive areas (ESAs). ILA is also aimed at reducing causes of degradation to environmental quality due to rapid development and expansion of city limits which have either directly or indirectly affected environmental quality in Klang Valley. The ILA model is implemented through incorporation with the use of the What if? PSS which is a scenario base, policy-oriented planning support system that uses increasingly available GIS data to support community-based process of collaborative planning and collective decision making. This paper will discuss the approach, developed model and underlying concept of ILA and emphasize on the case study concerning the use of ILA for defining and mapping of ESAs. Several issues raised in the study will be discussed